Peach MYB7 activates transcription of the proanthocyanidin pathway gene encoding leucoanthocyanidin reductase, but not anthocyanidin reductase - Zhou, Hui; Lin-Wang, Kui; Liao, Liao; Gu, Chao; Lu, Ziqi; Allan, Andrew C.; Han, Yuepeng (Frontiers in Plant Science, 2015)
Proanthocyanidins (PAs) are a group of natural phenolic compounds that have a great effect on both flavour and nutritious value of fruit. It has been shown that PA synthesis is regulated by R2R3-MYB transcription factors (TFs) via activation of PA-specific pathway genes encoding leucoanthocyanidin reductase (LAR) and anthocyanidin reductase (ANR). Here, we report the isolation and characterization of a MYB gene designated PpMYB7 in peach. The peach PpMYB7 represents a new group of R2R3-MYB genes regulating PA synthesis in plants. It is able to activate transcription of PpLAR1 but not PpANR, and has a broader selection of potential bHLH partners compared with PpMYBPA1. Transcription of PpMYB7 can be activated by the peach basic leucine-zipper 5 TF (PpbZIP5) via response to ABA. Our study suggests a transcriptional network regulating PA synthesis in peach, with the results aiding the understanding of the functional divergence between R2R3-MYB TFs in plants.